Towards a Reconciliation of the Empirical Evidence on the Monetary Approach to Exchange Rate Determination - DeJong, David N.; Husted, Steven (The Review of Economics and Statistics, 1993)
David N. DeJong, Steven Husted, Towards a Reconciliation of the Empirical Evidence on the Monetary Approach to Exchange Rate Determination, The Review of Economics and Statistics, Vol. 75, No. 1 (Feb., 1993), pp. 123-128